Endometriosis Patients Have an Increased Risk of Experiencing Long-Covid Symptoms: Results from a Cross-Sectional Multicenter Study - Anna Cirkel; Hartmut Göbel; Carl Göbel; Ibrahim Alkatout; Ahmed Khalil; Sascha Baum; Norbert Brüggemann; Achim Rody; Christoph Cirkel (Women's Health Reports)
Background: Women are more at risk for developing long-term symptoms after a COVID-19 infection. Only limited data are available for patients with coexisting endometriosis and/or menstrual pain symptoms. Study Design: A total of 840 premenopausal women with menstrual pain and/or endometriosis were included in this observational cross-sectional study using an online survey platform. Results: A total of 840 women with menstrual pain (mean age 30.7 ± 6.9, 15–54 years) were studied. Of these, 714 (84.2%) had a COVID-19 infection, 123 did not (14.5%). A total of 312 subjects had acute COVID-19 (AC) with symptoms ≤4 weeks (43.7%), 132 (18.5%) developed postacute COVID-19 syndrome (PC), and 88 (12.3%) had “long Covid” (LC). There were no statistical differences regarding number of vaccination shots between the three groups AC, PC, and LC. A total of 582 patients with surgically confirmed endometriosis (SCE) showed a twofold increased risk of LC [odds ratio (OR): 2.12, 2.18–3.84] in comparison with AC subjects. In SCE the comorbidity anxiety disorder (OR: 2.08, 1.14–3.81) and depression (OR: 2.02, 1.15–3.56) further increased the risk of LC. LC subjects had a significantly higher disturbance level of menstrual pain (p = 0.002), were more restricted in job (p < 0.001), leisure (p = 0.002), and family activities (p < 0.001), and had a higher number of endometriosis surgeries (p = 0.003). Conclusion: Subjects with SCE had a twofold increased risk of LC (in comparison to subjects with nonconfirmed endometriosis menstrual pain). In patients with SCE concomitant diagnosis of depression or anxiety disorder further twice-fold increased risk of LC. Further studies are needed if it is possible to reduce LC risk by improving the treatment of those secondary diagnoses and whether the type of endometriosis treatment can reduce LC occurrence (holistic, coanalgetic, hormonal).